2011
DOI: 10.1068/a44105
|View full text |Cite
|
Sign up to set email alerts
|

A Longitudinal Analysis of Moving Desires, Expectations and Actual Moving Behaviour

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
116
0
7

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 108 publications
(127 citation statements)
references
References 41 publications
4
116
0
7
Order By: Relevance
“…Existing studies have shown that the ability to act upon a desire to move is heavily dependent upon the micro-context of the household (Buck, 2000;Coulter et al, 2011;Landale and Guest, 1985). Characteristics such as income, housing tenure and the caring, work and social ties of household members all condition how easily households are able to move when this is desired by one or more household members (Coulter et al, 2012).…”
Section: Residential Mobility Within a Life Course Frameworkmentioning
confidence: 99%
See 2 more Smart Citations
“…Existing studies have shown that the ability to act upon a desire to move is heavily dependent upon the micro-context of the household (Buck, 2000;Coulter et al, 2011;Landale and Guest, 1985). Characteristics such as income, housing tenure and the caring, work and social ties of household members all condition how easily households are able to move when this is desired by one or more household members (Coulter et al, 2012).…”
Section: Residential Mobility Within a Life Course Frameworkmentioning
confidence: 99%
“…Influenced by these pioneering studies, a growing body of work has sought to investigate the links between mobility decision-making and subsequent moving behaviour. Several studies have examined both who desires to move and how these expressed moving desires affect the subsequent moving behaviour of households (Buck, 2000;Coulter et al, 2011;Ferriera & Taylor, 2009;Landale & Guest, 1985).…”
Section: Residential Mobility Within a Life Course Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…In this framework individuals hold relatively unconstrained space desires which are shaped by the ways in which housing requirements are formulated and evaluated within the context of distinct cultural preferences such as patrilocal traditions. The likelihood of realizing these desires is then self-reflexively assessed through considerations of resource access and the availability and affordability of housing, leading individuals to adapt their desire into a more constrained but more realistic space expectation (Coulter et al, 2011). Crucially, the translation of space desires into space expectations is a relational process as expectations are constructed, validated and normalized through interactions and comparisons with similar others (Fuller et al, 1993;Hagerty and Veenhoven, 2003).…”
Section: Differentiated Associations Across Socio-economic Gradientsmentioning
confidence: 99%
“…Analysis of the mobility of couples also illustrates that moves often take place which are desired by one member of a household, but not by others. Meaningful analysis of motivations for, and satisfaction with, mobility experiences therefore needs to be sharpened by focusing on movers who actually desire to move rather than, as is so often the case, analysing the 'reasons' and 'experiences' of all movers in an aggregated and uniform fashion (Coulter et al, 2011).…”
Section: Life Satisfaction and Geographical Mobilitymentioning
confidence: 99%